Indeks massa tubuh (IMT) dan lingkar lengan atas (LLA) dengan kadar hemoglobin pada ibu hamil trimester I - Fitri Kalfaria; Anita Rahmawati; Ana Kurniati (Jurnal Kesehatan Ibu dan Anak, 2015)
Compared to the 2007 maternal mortality rate of 208/100.000 birth rates, the 2012 maternal mortality rate in Indonesia experience an increase to of the 359/100.000 2007 birthrates. The main factors of maternal mortality is a bleeding possibilily cause by anemia because the red blood cell are lacking due to the decreasing hemoglobin. In 2012 the highest case of anemia in DIY is recorded to take place in the Bantul Regency. Anemia can be seen from the haemoglobin level and influenced by the nutrient status of moters. for this researcvh, analitiycal obsevational study is used with cross sectional approach. This research is conducted at the Public Health Center of Dlingo II, the regency of Bantul. The samples of this researvch ate pergnant mother on the first trimester. most pregnant mother whose data ate taken for this research have the status of body mass of 58.57% (good nutrient), upper arm measurment of 84.28% (good nutrient) and hemoglobin level lebel of 60% (not normal). from the cross table, most samples are found to have the body mass index with good nutrient but without normal hemoglobin level of 37.14%, and most samples have the upper arm measurement with good nutrient but without normal hemoglobin level of 48,58%. The statistic test result of body mass index and hemoglobin level shows the grades of Chi Square = 0,481, and p=0.488. The statistic test result of the upper arm measurement and hemoglobin level shows the grades of Chi Square = 0.881, and p=0.348. The research result shows that there is no relationship between body mass index as well as upper arm measurement and hemoglobin level found on the first-trimesster pregnant mothers.